The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1001/archopht.117.4.513
|View full text |Cite
|
Sign up to set email alerts
|

Human T-Cell Lymphotropic Virus Type 1 Infection and Ocular Manifestations in São Paulo, Brazil

Abstract: Although human T-cell lymphotropic virus type 1 (HTLV-1)-associated uveitis has been well recognized in Japan, related studies in Brazil are scarce. We performed a serologic survey for HTLV-1 infection among patients with uveitis and investigated the ocular findings in HTLV-1-asymptomatic carriers.Methods: One hundred ninety serum samples from patients with uveitis of determined (n = 137) and undetermined origins (n = 53

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
2
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 30 publications
4
18
2
2
Order By: Relevance
“…Dentre as várias formas de uveíte, a mais comum é a uveíte intermediária (21) . A soroprevalência para o HTLV-I/II, em nosso meio, em pacientes com uveíte de etiologia indeterminada varia de 1,8% a 3,6%, e em doadores de sangue é de 0,32%, sugerindo que a infecção por este retrovírus é dez vezes maior em pacientes com uveíte do que em doadores de sangue (22) . Desta forma, o HTLV-I/II deve ser lembrado como um possível agente etiológico de uveíte.…”
Section: Resultsunclassified
“…Dentre as várias formas de uveíte, a mais comum é a uveíte intermediária (21) . A soroprevalência para o HTLV-I/II, em nosso meio, em pacientes com uveíte de etiologia indeterminada varia de 1,8% a 3,6%, e em doadores de sangue é de 0,32%, sugerindo que a infecção por este retrovírus é dez vezes maior em pacientes com uveíte do que em doadores de sangue (22) . Desta forma, o HTLV-I/II deve ser lembrado como um possível agente etiológico de uveíte.…”
Section: Resultsunclassified
“…However, in São Paulo, Yamamoto et al 35 observed a KCS prevalence of 2.8% in infected carriers. This contradictory result could be explained by the fact that these HTLV-1 infected individuals did not have TSP/HAM.…”
Section: Discussionmentioning
confidence: 96%
“…Interestingly, HAU was not diagnosed in this study, even in patients with high PVL, corroborating other studies performed in Brazil that found a lower prevalence of HAU, compared to Japanese studies. 10,11,41,42 It is possible that genetic background could play a role in the difference HAU prevalences.…”
Section: Discussionmentioning
confidence: 99%